School Archive Management System: A Case Study - Muhammad Dimas Fahrezi (Jurnal Sinar Edukasi, 2020)
This research is motivated by problems related to the school archive management system at SMP Negeri 7 Muaro Jambi, including a lack of employee knowledge about indexes, facilities, and infrastructure, as well as minimal administrative staff for managing archives. The objectives of this study are (1) to describe the procedures for managing archives at SMP Negeri 7 Muaro Jambi; (2) to describe the archive storage space at SMP Negeri 7 Muaro Jambi; (3) to describe the archive management facilities at SMP Negeri 7 Muaro Jambi; (4) to describe the archive officers in managing archives at SMP Negeri 7 Muaro Jambi. This study uses a qualitative descriptive method with data collection techniques, namely: the interview method, observation, and documentation. Data analysis techniques in this study include data reduction, data display, and conclusion drawing/verification. The results of this study are first, the archive management procedure at SMP Negeri 7 Muaro Jambi which consists of: a) archive creation starts from the creation of the archive then managed/grouped and made into an archive; b) management of incoming mail, via WhatsApp then printed at school and given to the destination address of the letter; c) management of outgoing mail, the letter is first examined by the Principal of SMP Negeri 7 Muaro Jambi, corrected, numbered, recorded in the agenda book and then signed by the Principal; d) use of archives, copied or photographed archives to be used and returned to their original place; e) archive maintenance has not been carried out special maintenance or has not been maximized f) archive reduction, there has been no archive reduction. Second, SMP Negeri 7 Muaro Jambi does not yet have a dedicated archive storage room. Third, archive management facilities are inadequate in terms of quality and quantity. Fourth, the lack of administrative staff as archive officers affects the accuracy and neatness in managing archives.